KONSTRUKSI CITRA MASKULINITAS CALON PRESIDEN (Study Analisis Framing model Gamson dan Modigliani pada Pemberitaan Koran harian Kompas dan Jawa Pos Edisi Juni 2014) - Nanang Mizwar Hasyim (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Realize it or not masculinity is the result of the construction of the mass media. Some studies on the media's role in changing people's behavior have a significant effect. In a political world dominated by the role of the mass media, which in this case there are news that is considered frequently accentuate the dominance of masculinity for production areas controlled by the masculine. As a result, the news content presents the erotic images of male primacy that became the main picture and appears in the symbols of male strength in the domain of social and political control of space that cannot be separated from the stereotypes that exist in society. This paper is an analysis’s against the practices of masculinity second image production Presidential candidate Joko Widodo and Prabowo conducted by the newspaper Jawa Pos and Kompas in reporting PILPRES 2014 campaign.